2019
DOI: 10.1007/s00404-019-05387-3
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-concordant chemotherapy in patients with hormone receptor-positive and node-positive, early breast cancer leads to better overall and metastases-free survival with limited benefit in elderly patients

Abstract: Purpose The German guideline for breast cancer recommends using chemotherapy (CHT) in patients with hormone receptorpositive and node-positive, invasive breast cancer. The aim of this study was to analyse the effects of CHT in this patient group on overall survival (OS) and distant metastases-free survival (DMFS), especially considering the 70-year threshold. Methods 1772 patients from the clinical cancer registry Regensburg (Germany) with hormone receptor-positive and nodepositive, invasive breast cancer diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
(23 reference statements)
1
12
0
1
Order By: Relevance
“…After weighted, we found that chemotherapy improved survival, especially in women aged 70-74 years, but not significantly in women 75 years or older. These results are similar to those in other studies that have shown benefit of chemotherapy in appropriately selected patients (15)(16)(17)(18), but that the benefit decreases with aging (19,20). At the same time, the physiologic changes of aging increase the risk of adverse effects, together with an increased risk of hospitalization (21).…”
Section: Discussionsupporting
confidence: 89%
“…After weighted, we found that chemotherapy improved survival, especially in women aged 70-74 years, but not significantly in women 75 years or older. These results are similar to those in other studies that have shown benefit of chemotherapy in appropriately selected patients (15)(16)(17)(18), but that the benefit decreases with aging (19,20). At the same time, the physiologic changes of aging increase the risk of adverse effects, together with an increased risk of hospitalization (21).…”
Section: Discussionsupporting
confidence: 89%
“…Andere Studien aus Deutschland konnten zeigen, dass positive Ausprägungen von Prozessqualitätsindikatoren mit positiven Ergebnissen für Patienten assoziiert sind. Beispielhaft genannt werden sollen hierzu aktuelle Analysen aus dem Traumaregister, einem klinischen Krebsregister und den Schlaganfallregistern, die jedoch alle nicht zu den verpflichtenden QS-Maßnahmen zählen [ 18 20 ]. Aber auch anhand von Daten der eQS konnte gezeigt werden, dass positive Indikatorausprägungen mit besseren Versorgungsstrukturen und auch besseren Patientenerfahrungen einhergehen [ 21 ].…”
Section: Ergebnisseunclassified
“…Sixty-seven papers were selected for full-text review; 64 from the electronic databases and three were selected from the reference list of an earlier systematic review [24]. Of these, 16 papers met the study eligibility criteria [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The stages of the study selection are presented in Figure 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…Table 1 summarises the characteristics of the 16 publications. The papers had adopted three main study designs: population-based cohort studies which used cancer registry databases (N = 8) [31-35, 37, 38, 42], multi-centre cohort studies (N = 5) [27,36,[39][40][41], or case series which used data from single institution databases (N = 3) [28][29][30]. Ten studies [27,29,31,32,35,[37][38][39][40][41] reviewed adherence to clinical guidelines, whilst six [28,30,33,34,36,42] used quality indicators or standards.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%